The Relationship between Emotional Intelligence, Critical Thinking, and Speaking Ability at Junior High School - David Suhendra; Tahrun Tahrun; Mulyadi Mulyadi (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to find out the relationship between students' emotional intelligence, critical thinking, and their speaking ability at state junior high school 1 of Belimbing. The population of this study was all the eighth-grade students of State Junior High School 1 of Belimbing in the academic year 2022/2023 which consists of five classes, and 30 students in the eighth grade were chosen as the sample. This study applied the correlational research design. Questionnaires and test were used to collect the data. They were analyzed by using Pearson Product Moment and multiple regression analysis. The result showed: first, there was a significant and strong correlation between critical thinking and speaking ability of the eighth-grade students of State Junior High School 1 of Belimbing, second, there was a significant and strong correlation between emotional intelligence and speaking ability of the eighth-grade students of State Junior High School 1 of Belimbing, and third, there was a significant correlation among critical thinking and emotional intelligence simultaneously on speaking ability of the eighth-grade students of State Junior High School 1 of Belimbing.